2019
DOI: 10.1021/acs.jpcb.8b11202
|View full text |Cite
|
Sign up to set email alerts
|

Beyond the Tradeoff: Dynamic Selectivity in Ionic Transport and Current Rectification

Abstract: Traditionally, ion-selectivity in nanopores and nanoporous membranes is understood to be a consequence of Debye overlap, in which the Debye screening length is comparable to the nanopore radius somewhere along the length of the nanopore(s). This criterion sets a significant limitation on the size of ion-selective nanopores, as the Debye length is on the order of 1 − 10 nm for typical ionic concentrations. However, the analytical results we present here demonstrate that surface conductance generates a dynamical… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
96
2
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(106 citation statements)
references
References 44 publications
(299 reference statements)
2
96
2
2
Order By: Relevance
“…28 Secondly, we demonstrate that pressure induced-fluid flow produces ionic current rectification despite the lack of the usually required geometrical asymmetry in the pore. 5,7 This is opposite to the so far reported role of pressure in reducing ICR in asymmetrical nanopores 18,19 .…”
Section: Introductioncontrasting
confidence: 87%
See 2 more Smart Citations
“…28 Secondly, we demonstrate that pressure induced-fluid flow produces ionic current rectification despite the lack of the usually required geometrical asymmetry in the pore. 5,7 This is opposite to the so far reported role of pressure in reducing ICR in asymmetrical nanopores 18,19 .…”
Section: Introductioncontrasting
confidence: 87%
“…where d is the diameter of the nanopore, L the thickness of the membrane, and σ the bulk conductance of the solution. 33,34 One measure of the nonlinearity in ion transport is the ionic current rectification (ICR) ratio 5,7 which we define as:…”
Section: Degassed Solutionmentioning
confidence: 99%
See 1 more Smart Citation
“…This effect is becoming increasingly important as the pore size increases and helps to maintain good power generation in large nanopores. Along the same line, recent work has analytically shown that strong surface conductance generates a dynamic ion selectivity, which is defined through Dukhin, rather than EDL, overlap and is responsible for the maintenance of good ion selectivity in larger pores 24 .…”
Section: Discussionmentioning
confidence: 93%
“…an asymmetric surface charge or an asymmetric geometry. Such behavior is expected to occur in the regime where the Dukhin number is of order one and asymmetric along the channel 154 : the Dukhin number is defined here as Du = Σ/c s h, where Σ is the surface charge density, c s the bulk salt concentration and h a characteristic channel dimension. It quantifies the importance of surface versus bulk electric conduction.…”
Section: Osmotic Diodes and Osmotic Pressure Rectificationmentioning
confidence: 99%